Developing a culturally tailored stroke prevention walking programme for Korean immigrant seniors: a focus group study. (17th January 2016) - Choi, Sarah E.; Kwon, Ivy; Chang, Emiley; Araiza, Daniel; Thorpe, Carol Lee; Sarkisian, Catherine A.
Abstract : Objectives: To gain better understanding of (i) beliefs and knowledge about stroke; (ii) attitudes about walking for stroke prevention; and (iii) barriers and facilitators to walking among Korean seniors for the cultural tailoring of a stroke prevention walking programme. Background: Physical inactivity is a major risk factor for stroke. Korean immigrant seniors are one of the most sedentary ethnic groups in the United States. Design: An explorative study using focus group data. Twenty‐nine Korean immigrant seniors (64–90 years of age) who had been told by a doctor at least once that their blood pressure was elevated participated in 3 focus groups. Each focus group consisted of 8–11 participants. Methods: Focus group audiotapes were transcribed and analysed using standard content analysis methods. Results: Participants identified physical and psychological imbalances (e.g. too much work and stress) as the primary causes of stroke. Restoring 'balance' was identified as a powerful means of stroke prevention. A subset of participants expressed that prevention may be beyond human control. Overall, participants acknowledged the importance of walking for stroke prevention, but described barriers such as lack of personal motivation and unsafe environment. Many participants believed that providing opportunities for socialisation while walking and combining walking with health information sessions would facilitate participation in and maintenance of a walking programme. Conclusions: Korean immigrant seniors believe strongly that imbalance is a primary cause of stroke. Restoring balance as a way to prevent stroke is culturally special among Koreans and provides a conceptual base in culturally tailoring our stroke prevention walking intervention for Korean immigrant seniors. Implications for practice: A stroke prevention walking programme for Korean immigrant seniors may have greater impact by addressing beliefs about stroke causes and prevention such as physical and psychological imbalances and the importance of maintaining emotional well‐being.